2012
DOI: 10.4103/2279-042x.108374
|View full text |Cite
|
Sign up to set email alerts
|

Serum adenosine deaminase in patients with rheumatoid arthritis treated with methotrexate

Abstract: Objective:Recently, adenosine deaminase (ADA) is introduced as helpful marker in diagnosis, prognosis, and monitoring of treatment in rheumatoid arthritis (RA). The aim of this study was to determine the efficacy of the serum ADA in diagnosis, prognosis, and monitoring of treatment with methotrexate (MTX) in RA.Methods:This was a self-controlled clinical trial conducted in university hospitals of Isfahan, Iran. The serum level of ADA, erythrocyte sedimentation rate (ESR), and rheumatoid factor (RF) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
(26 reference statements)
1
15
1
Order By: Relevance
“…In our previous study, we found inverse correlation between serum ADA level and ESR during acute phase of JIA and between serum ADA level and WBC counts after disease control (25). Salesi et al reported significant correlation between serum ADA and ESR (15), but the result of our recent study was compatible with that of Sari et al (19). Vinapamula et al found significant positive correlation between serum ADA and CRP in RA patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our previous study, we found inverse correlation between serum ADA level and ESR during acute phase of JIA and between serum ADA level and WBC counts after disease control (25). Salesi et al reported significant correlation between serum ADA and ESR (15), but the result of our recent study was compatible with that of Sari et al (19). Vinapamula et al found significant positive correlation between serum ADA and CRP in RA patients.…”
Section: Discussionsupporting
confidence: 81%
“…Adenosine deaminase (ADA) is one of the main enzymes of purine metabolic pathway, and is responsible to metabolize adenosine. ADA represents an exclusive checkpoint in the extracellular adenosine regulation and, consequently, in the control of immune system activity through its modulation of adenosine pathways (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Serum ADA levels in patient and control groups were determined and the relation between ADA level and disease activity parameters were evaluated. Although the exact effect of MTX on the ADA enzymatic activity is not clearly understood, it is assumed that in purine enzyme metabolic pathway, MTX increases adenosine and inhibits ADA both directly and indirectly [ 10 ]. Therefore the RA group was divided into two groups as patients receiving MTX and patients on drugs other than MTX.…”
Section: Methodsmentioning
confidence: 99%
“…There are conflicting reports about the relationship of ADA and disease activity parameters in the English literature [ 5 - 16 ]. Serum ADA was reported to be increased in serum and synovial fluid of RA patients compared with non-inflammatory arthritic conditions [ 7 , 10 , 11 ]. ADA has been suggested as a prediction marker or a useful biochemical marker of inflammatory process in patients with RA [ 13 , 14 ], while some studies did not find a correlation between ADA levels and disease activity markers [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the anti-inflammatory effects of EA seem to be similar to the effects of methotrexate. Both treatments result in an increase in the extracellular concentration of adenosine and the downregulation of ADA [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%